2015
DOI: 10.4103/0973-1296.168986
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pharmacodynamic and Pharmacokinetic Interaction of Aqueous Extract of Cassia auriculata L. and Metformin in Rats

Abstract: Background:Cassia auriculata L. (CA) leaf extract might increase the body's production of insulin thereby suppressing the elevated blood glucose and lipid levels in diabetic rats. CA has been used as dietary supplement in India from ancient times.Objective:The present study was to elucidate the synergistic pharmacodynamic (PD) and pharmacokinetic (PK) interaction of metformin (MT) with CA.Materials and Methods:A simple, precise reverse phase high performance liquid chromatography - UV detection mode method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The traditionally prepared hydro-alcoholic extract did not show any change in the pharmacokinetics of metformin. Furthermore, Elango et al (2015) demonstrated the pharmacodynamic and pharmacokinetic interactions on co-administration of metformin and aqueous extract of Senna auriculata (L.) Roxb. leaves.…”
Section: Herbal Drug-drug Interactionsmentioning
confidence: 99%
“…The traditionally prepared hydro-alcoholic extract did not show any change in the pharmacokinetics of metformin. Furthermore, Elango et al (2015) demonstrated the pharmacodynamic and pharmacokinetic interactions on co-administration of metformin and aqueous extract of Senna auriculata (L.) Roxb. leaves.…”
Section: Herbal Drug-drug Interactionsmentioning
confidence: 99%